El papel del periodismo de datos en el combate contra la desinformación – caso de estudio periodo 2022. - Noboa Heredia, Paulina Alejandra (2025)
This research aimed to analyze data journalism's role in combating disinformation during the post-pandemic health recovery period in the print media outlet Diario La Prensa de Riobamba, from January to December 2022. To this end, a mixed methodology was implemented, employing deductive and analytical methods, relying on techniques such as interviews and a content analysis matrix, which enrich the research. Additionally, three professionals on the topic were interviewed to provide relevant information. Subsequently, the research results were obtained through a content analysis matrix for news articles during the aforementioned period, revealing a decrease in the number of printed materials. Furthermore, upon analyzing the data obtained, it was concluded that the Ministry of Public Health and Diario La Prensa had to migrate to other digital platforms to maintain their audience and continue reporting reliably. The research culminates with creating a scientific article derived from this research.